Exploring the chemotherapeutic potential of currently used kinase inhibitors: An update - Naik, Rajashri R.; Shakya, Ashok K. (Frontiers in Pharmacology, 2023)
Protein Kinase is enzymes that transfer phosphate to protein and result in the modification of the protein. The human genome encodes around 538 kinase. Kinases have a role in maintaining a number of cellular processes, including the control of the cell cycle, metabolism, survival, and differentiation. Protein kinase dysregulation causes a number of diseases, and it is discovered that numerous kinases are deregulated in cancer. The oncogenic potential of the kinases is increased by a number of processes, including over expression, relocation, fusion point mutations, and disruption of upstream signaling. Understanding the mechanism or role played by the kinases has led to the development of the large number of kinase inhibitors with promising clinical benefits. In this review, we will be discussing the FDA approved kinase inhibitors, their mechanism, clinical benefits, side effects, and how the challenges are explored and future prospects in the discovery of kinase inhibitors.